Bank-specific capital requirements: short and long-run determinants - Alves, Carlos Francisco (2023)
This paper studies the determinants of the Pillar 2 capital requirements (P2R) of banks directly supervised by the ECB between 2016 and 2021. Drawing on the ECB’s Supervisory Review and Evaluation Process (SREP) to identify the list of potential drivers of P2R, we estimate the impact on P2R by employing a method that separates long-run from short-run determinants. Our results suggest that in (i) the long-run, the P2R is mostly driven by credit risk, funding risk, and governance, whereas (ii) profitability and market risk seem to be the main short-run determinants of P2R. Furthermore, we find evidence that suggests the supervisor incorporates proportionality in the P2R decisions. Effectively, our sensitivity analyses show considerable differences in the long-run determinants of P2R according to the level of capital, size, and access to market funding of supervised entities.